Stratigraphy of the Sabhaya khola region, Sankhuha Sabha district, Eastern Nepal (Journal of Nepal Geological Society, 1982)
Litho-stratigraphy of Sabhaya Khola region of eastern Nepal is worked out. The area is divided by thrusts into three main units viz; Milke Gneiss, Kathmandu Complex and Nuwakot Complex. The units are further subdivided into groups    and formations mainly based on lithological characteristics. An attempt is also made to correlate these rocks with previous investigations in and adjacent to the present study area.Economic deposits of almandine garnet occur within a N-S extending narrow zone in the Chainpur Group of Kathmandu Complex. The mineralization in the zone is considered to be controlled stratigraphically. Also, gem bearing pegrnatites occur in a definite stratigraphic horizon within the Phakuwa Group of Kathmandu Complex, just below the Main Central Thrust.